2018
DOI: 10.1002/2017ja024481
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Gravity Waves in Polar Mesospheric Clouds Using Tomographic Reconstructions of AIM Satellite Imagery

Abstract: This research presents the first application of tomographic techniques for investigating gravity wave structures in polar mesospheric clouds (PMCs) imaged by the Cloud Imaging and Particle Size instrument on the NASA AIM satellite. Albedo data comprising consecutive PMC scenes were used to tomographically reconstruct a 3‐D layer using the Partially Constrained Algebraic Reconstruction Technique algorithm and a previously developed “fanning” technique. For this pilot study, a large region (760 × 148 km) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 82 publications
(172 reference statements)
0
16
0
Order By: Relevance
“…However, the concept of 3-D tomography with sidewardslooking airborne instruments or sub-limb instruments (Song et al, 2017;Hart et al, 2018) is quite different and, thus, may exhibit different characteristics. In 2-D tomography a volume is reconstructed from rearwardlooking measurements on a moving platform that slice the volume into multiple 2-D images.…”
Section: Full Angle Tomography (Fat)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the concept of 3-D tomography with sidewardslooking airborne instruments or sub-limb instruments (Song et al, 2017;Hart et al, 2018) is quite different and, thus, may exhibit different characteristics. In 2-D tomography a volume is reconstructed from rearwardlooking measurements on a moving platform that slice the volume into multiple 2-D images.…”
Section: Full Angle Tomography (Fat)mentioning
confidence: 99%
“…This model was developed to efficiently handle imager instruments and tomographic retrievals. It is based on JURAS-SIC (Hoffmann, 2006), which was previously used as a forward model for the evaluation of several satellite-and airborne remote-sensing experiments (e.g. Eckermann et al, 2006;Hoffmann et al, 2008;Weigel et al, 2010;Kalicinsky et al, 2013;Ungermann et al, 2016).…”
Section: Gloria Measurement Simulatormentioning
confidence: 99%
“…In the stratosphere, techniques have been developed to overcome these limitations. The AIRS instrument on board the AQUA satellite measures upwelling radiation in a large number of spectral channels, and gravity waves have been retrieved from the upper troposphere to the mid-stratosphere (Hoffmann and Alexander, 2009;Gong et al, 2012). Additional techniques have been developed to maximize horizontal wave information from AIRS, utilizing either across-track nadir scans (Wright et al, 2017) or data from multiple satellite tracks .…”
Section: Satellite Measurements Of Gravity Wavesmentioning
confidence: 99%
“…This model was developed to efficiently handle imager instruments and tomographic retrievals. It is based on JURAS-SIC (Hoffmann, 2006), which was previously used as a forward model for the evaluation of several satellite-and airborne remote-sensing experiments (e.g. Eckermann et al, 2006;Hoffmann et al, 2008;Weigel et al, 2010;Kalicinsky et al, 2013;Ungermann et al, 2016).…”
Section: Gloria Measurement Simulatormentioning
confidence: 99%
“…Former studies demonstrated the feasibility of 2-D tomography of rearward-looking satellite instruments for the retrieval of 3-D atmospheric structures such as GWs (Degenstein et al, 2004;Ungermann et al, 2010a;Hultgren et al, 2013). However, the concept of 3-D tomography with sidewardslooking airborne instruments or sub-limb instruments (Song et al, 2017;Hart et al, 2018) is quite different and, thus, may exhibit different characteristics. In 2-D tomography a volume is reconstructed from rearwardlooking measurements on a moving platform that slice the volume into multiple 2-D images.…”
Section: Full Angle Tomography (Fat)mentioning
confidence: 99%